Interpreting Monastic Cartularies in Northwest Europe, 900-1200: Thirty Years of Scholarship - Robert Berkhofer (Studia Historica. Historia Medieval)
Since the publication of Les cartulaires in 1993, the study of cartularies has evolved in two main directions: as part of a broader documentary culture and studying regional or textual patterns using digital tools and postmodern approaches. This article offers an overview of interpretive trends since then, focusing on monastic cartularies in northwestern Europe in the Central Middle Ages. It outlines the diverse discourses incorporated in these cartularies, involving patrimony, commemoration, communal identity, and history. It then explores the variable forms of monastic cartularies, including smaller groupings of charters, and their functions. It argues that monastic writers carefully framed their re-presentation charters from their archives, to impart multiple messages to their medieval audiences.